Pediatric Urolithiasis: Current Surgical Strategies and Future Perspectives - Irene Paraboschi; Michele Gnech; Erika Adalgisa De Marco; Dario Guido Minoli; Carolina Bebi; Stefano Paolo Zanetti; Gianantonio Manzoni; Emanuele Montanari; Alfredo Berrettini (Frontiers Media S.A., 2022)
New technological innovations and cutting-edge techniques have led to important changes in the surgical management of pediatric urolithiasis. Miniaturized technologies and minimally invasive approaches have been increasingly used in children with urinary stones to minimize surgical complications and improve patient outcomes. Moreover, the new computer technologies of the digital era have been opening new horizons for the preoperative planning and surgical treatment of children with urinary calculi. Three-dimensional modeling reconstructions, virtual, augmented, and mixed reality are rapidly approaching the surgical practice, equipping surgeons with powerful instruments to enhance the real-time intraoperative visualization of normal and pathological structures. The broad range of possibilities offered by these technological innovations in the adult population finds increasing applications in pediatrics, offering a more detailed visualization of small anatomical structures. This review illustrates the most promising techniques and devices to enhance the surgical treatment of pediatric urolithiasis in children, aiming to favor an early adoption and to stimulate more research on this topic.